The symbolism of colour in the interpretation of a drawing in Gestalt - Tatiana A. Syrovatskaya, Lubov V. Karotovskaya, Shatalova, Lubo I, Sergey I. Maslakov,; Karina E. Panasenko, Anna N. Doborovich, (Opción, 2019)
The article investigates the peculiarities of colour symbolism and semantics that might be applied in the interpretation of a projective drawing in Gestalt. As a result, a child’s drawing is a kind of figurative art; this is something that has to evoke not just the viewer’s thoughts and feelings about the depicted figurative material. In conclusion, we can supplement a diagnostic component part with a new approach of psychodiagnosis problem-solving of individual and typological features of personality peculiarities in the modern pedagogical educational process.